A Model for Customer Variety-Seeking Behavior in Online Retail - Soleymani, Ali; Aghajani, Mojtaba; Landaran, Saeed (Management Strategies and Engineering Sciences, 2024)
Variety-seeking is the pursuit of new experiences and products by customers. This article aims to present a model for variety-seeking behavior among customers in online retail environments. The research conducted is applied in nature, descriptive-survey in data collection methodology, and quantitative in terms of data type. For data collection, a researcher-developed questionnaire was designed. The validity of the questionnaire was determined using the Content Validity Index (CVI), and reliability was assessed with Cronbach's alpha coefficient (0.78). The statistical population consisted of online retail customers, with an indefinite population size. A simple random sampling method was used to select a sample of 384 individuals from this population. The collected data were analyzed using model fit indices such as Goodness of Fit Index (GFI), Normed Fit Index (NFI), and Root Mean Square Error of Approximation (RMSEA), leading to the confirmation of the final research model. Causal factors, factors affecting competitor orientation, factors impacting sales decline, variety-seeking behavior factors, purchase-related factors, motivations for inclination toward new products, contextual factors, the setting and conditions under which variety-seeking behavior occurs, and marketing strategy all play roles in variety-seeking behavior among online retail customers. It is essential for business owners to investigate and reflect more deeply on the root causes of variety-seeking behavior to attract, retain, and increase their customer base. This approach involves considering these factors in the enhancement and diversification of their businesses in production, distribution, sales, and post-sales services.